Optimal Scheduling Model of WDM/OTN Network Transmission Line Based on Machine Learning - Jianhua Zhao; Jingquan Li; Huicong Fan; Wenxiao Li; Jingna Zhang; Xiaoyuan Dai (Journal of Control Science and Engineering)
In order to solve the problem that the influencing factors are difficult to parameterize in the design and development of WDM/OTN backbone network routing planning tools, the author proposes an optimal scheduling model for WDM/OTN network transmission lines based on machine learning. Using the machine learning classification algorithm as a tool, the weight coefficients of each constraint factor are extracted from the historical design decisions, and the routing parameter model is constructed, so as to realize the intelligent routing selection, through actual simulation analysis and engineering verification. Simulation results show that after the historical routing regression test, the path coincidence rate of the route obtained by the algorithm and the historical real decision-making route reaches 81%, and the resource hit rate reaches 84%, which meets the requirements for actual production. Conclusion. This method can accurately and effectively generate network weight parameters so that the software routing is more intelligent.